Balance control in lower extremity amputees during quiet standing: a systematic review - Ku, P.X.; Abu Osman, Noor Azuan; Wan Abas, W.A.B. (2014)
Postural control has been widely evaluated for the normal population and different groups over the past 20 years. Numerous studies have investigated postural control in quiet standing posture among amputees. However, a comprehensive analysis is lacking on the possible contributing factors to balance. The present systematic review highlights the current findings on variables that contribute to balance instability for lower extremity amputees.The search strategy was performed on PubMed, Web of Science, Medline, Scopus, and CINAHL and then followed by additional manual searching via reference lists in the reviewed articles. The quality of the articles was evaluated using a methodological quality assessment tool. This review included and evaluated a total of 23 full-text articles.Despite the inconsistencies in the methodological design of the studies, all articles scored above the acceptable level in terms of quality. A majority of the studies revealed that lower extremity amputees have increased postural sway in the standing posture. Asymmetry in body weight, which is mainly distributed in the non-amputated leg, was described. Aside from the centre of pressure in postural control, sensory inputs may be a related topic for investigation in view of evidence on their contribution, particularly visual input. Other balance-related factors, such as stump length and patients' confidence level, were also neglected. Further research requires examination on the potential factors that affect postural control as the information of standing postural is still limited. Â© 2013 The Authors.